Indexing grazing‐incidence X‐ray diffraction patterns of thin films: lattices of higher symmetry. Issue 2 (1st April 2019) - Simbrunner, Josef; Hofer, Sebastian; Schrode, Benedikt; Garmshausen, Yves; Hecht, Stefan; Resel, Roland; Salzmann, Ingo
Abstract : A general indexing procedure for grazing‐incidence X‐ray diffraction patterns recorded from fibre‐textured films is introduced for lattices of monoclinic and higher‐symmetry systems. The analytical mathematical expressions are given and their use is demonstrated in detail for two cases (monoclinic and orthorhombic). Abstract : Grazing‐incidence X‐ray diffraction studies on organic thin films are often performed on systems showing fibre‐textured growth. However, indexing their experimental diffraction patterns is generally challenging, especially if low‐symmetry lattices are involved. Recently, analytical mathematical expressions for indexing experimental diffraction patterns of triclinic lattices were provided. In the present work, the corresponding formalism for crystal lattices of higher symmetry is given and procedures for applying these equations for indexing experimental data are described. Two examples are presented to demonstrate the feasibility of the indexing method. For layered crystals of the prototypical organic semiconductors diindenoperylene and ( ortho ‐difluoro)sexiphenyl, as grown on highly oriented pyrolytic graphite, their yet unknown unit‐cell parameters are determined and their crystallographic lattices are identified as monoclinic and orthorhombic, respectively.